2019
DOI: 10.3390/w11112379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Large Irrigation Reservoir on Aquatic and Riparian Plants: A History of Survival and Loss

Abstract: Dammed rivers have unnatural stream flows, disrupted sediment dynamics, and rearranged geomorphologic settings. Consequently, fluvial biota experiences disturbed functioning in the novel ecosystems. The case study is the large irrigation reservoir Alqueva in Guadiana River, Southern Iberia. The study area was divided into three zones: upstream and downstream of the dam and reservoir. For each zone, species composition and land use and land cover (LULC) were compared before and after the Alqueva Dam implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It is part of the Guadiana basin with a total storage capacity of 4150 hm 3 [19]. It was built to be a strategic water reserve that would allow the reinforcement of water capacity, the supply to populations (drinking water), the irrigation of crops, and the production of electricity (hydroelectric production) [20]. With the construction of the Alqueva Multipurpose Development Project (AMDP), three subsystems for irrigation (Alqueva, Ardila, and Pedrógão) constituting the Alqueva Global Irrigation System (AGIS) were created [21].…”
Section: Study Areamentioning
confidence: 99%
“…It is part of the Guadiana basin with a total storage capacity of 4150 hm 3 [19]. It was built to be a strategic water reserve that would allow the reinforcement of water capacity, the supply to populations (drinking water), the irrigation of crops, and the production of electricity (hydroelectric production) [20]. With the construction of the Alqueva Multipurpose Development Project (AMDP), three subsystems for irrigation (Alqueva, Ardila, and Pedrógão) constituting the Alqueva Global Irrigation System (AGIS) were created [21].…”
Section: Study Areamentioning
confidence: 99%
“…The main conclusion of this review is that priority should be given to implementing sustainable planning and technological solutions to build facilities whose social benefits will largely outweigh any environmental losses. These should be subject to the most effective possible compensation [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. The need for ex ante impact assessments is emphasised, but also for studies to be repeated after a longer period of reservoir operation [69].…”
Section: R12-the Need To Resettle Peoplementioning
confidence: 99%
“…It is not insignificant to maintain baseflows (biological) on the outflow from the reservoir. The construction of large facilities of strategic importance for the whole country or region will always involve environmental impacts; however, studies of the large Alqueva reservoir have shown that many other factors have been superimposed on changes to the vegetation structure in its catchment, and that the recovery of important assemblages of endemic species is possible by adopting ecological-restoration solutions [73]. Such a measure has been implemented in the case of the Three Gorges Reservoir catchment, where there has been a change in microclimate favourable to the spread of vegetation [74].…”
Section: R12-the Need To Resettle Peoplementioning
confidence: 99%
“…Although riparian zones are highly dynamic ecosystems, relevant changes in the riparian woody strata usually require more than 5 years to be significantly detectable with the image resolution that was used in the current study. Other riparian woody vegetation analyses have been successfully conducted with similar temporal mismatch among images and field data [47]. As for differences in the spatial resolution, due to the coarser resolution used to develop the ARZ model, riparian patches appear larger, more homogeneous and less numerous, while with the MRZ layer, representative of the ground-truth, patches are smaller, more heterogeneous and in higher number (Figure 4).…”
Section: Drawbacks and Strengths Of Copernicus Data For The Assessment Of Riparian Forest Connectivitymentioning
confidence: 99%